Windows 8 : video quickstart - Schwartz, Steve (Peachpit Press, 2012)
"Microsoft has gone all in with Windows 8. The latest edition of the Windows operating system offers a modern way for users to interact with their PCs, tablets, and phones. This video is exactly what you need to get up to speed with Windows 8; its short, engaging lessons show Windows' new features in action and illustrate how to work with tiles, make your way around the desktop, work with control panels and settings, launching and switching among applications, and more. Along the way, the video covers how Internet Explorer 10 and other essential Windows 8 tools."--Resource description page.